PEMETAAN SEBARAN BAHAN GALIAN GOLONGAN C MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KABUPATEN BANJAR, KALIMANTAN SELATAN - Anisa Maulina; Nurlina Nurlina; Sri Cahyo Wahyono (Jurnal Fisika FLUX, 2014)
Abstract. Mining material of kind C include igneous rocks, sedimentary rocks and metamorphic rocks. These minerals are often used as industrial raw material. Geologically these minerals are to be found in Banjar Regency. Mining material of kind C can increase regional income. Concerning this, mapping of Mining material of kind C distribution is necessary. Method used for this is interpretation of Geological Map of Banjar Regency and stratigraphic analysis. Based on interpretation of geological map, Mining material of kind C found in Banjar Regency include sand, clay, quartz sandstone, quartzite, andesite, granite and serpentinit. Andesite distribution is found in Pitanak and Pauu formation with distributional area of 421 km². Granite distribution is found in Granite Formation with distributional area of 101 km². Quartz sandstone distribution is found in Tanjung Formation with distributional area of 81 km². Serpentinite distribution is found in Manunggul and Ultramafic rocks distribution with distributional area of 941 km². Quartzite distribution is found in Metamorphic Rocks with distributional area of 123 km². Sand and clay are found in Alluvium with distributional area of 1.430 km². Keywords: Banjar Regency, group C minerals, GIS